Nexus of Carbon Dioxide Emissions, Fossil Fuel, Foreign Direct Investments, and Exports to Renewable Energy: New Evidence from Singapore - Nguyen Thi Phuong Thu; Pham Xuan Hoa; Vu Ngoc Xuan (Migration Letters, 2023)
This paper investigates the intricate relationship between carbon dioxide (CO2) emissions, fossil fuel consumption, foreign direct investments (FDI), exports, and the shift towards renewable energy in the context of Singapore. The study uses the unrestricted fixed and random panel data method. Data in this paper is collected from the World Bank from 2000 to 2022. This paper also investigates the intricate nexus of carbon dioxide (CO2) emissions, fossil fuel consumption, foreign direct investments (FDI), exports and renewable energy consumption, and Singapore’s shift towards renewable energy. As a dynamic and rapidly growing economy, Singapore’s lessons provide valuable insights into the challenges and opportunities of balancing economic development, environmental sustainability, and the global movement to renewable energy sources. Utilizing comprehensive data sets, statistical analyses, and econometric modeling, we explore the nexus between these critical variables to gain a nuanced understanding of Singapore’s evolving energy landscape. The empirical results give the suggested policy implication for the Singapore government and lessons learned for other countries.